An arginine/lysine-rich motif is crucial for VCP/p97-mediated modulation of ataxin-3 fibrillogenesis. - Boeddrich, A.; Gaumer, S.; Haacke, A.; Tzvetkov, N.; Albrecht, M.; Evert, B.O.; Muller, E.C.; Lurz, R.; Breuer, P.; Schugardt, N.; Plassmann, S.; Xu, K.; et al. (The EMBO Journal, 2006)
Arginine/lysine-rich motifs typically function as targeting signals for the translocation of proteins to the nucleus. Here, we demonstrate that such a motif consisting of four basic amino acids in the polyglutamine protein ataxin-3 (Atx-3) serves as a recognition site for the interaction with the molecular chaperone VCP. Through this interaction, VCP modulates the fibrillogenesis of pathogenic forms of Atx-3 in a concentration-dependent manner, with low concentrations of VCP stimulating fibrillogenesis and excess concentrations suppressing it. No such effect was observed with a mutant Atx-3 variant, which does not contain a functional VCP interaction motif. Strikingly, a stretch of four basic amino acids in the ubiquitin chain assembly factor E4B was also discovered to be critical for VCP binding, indicating that arginine/lysine-rich motifs might be generally utilized by VCP for the targeting of proteins. In vivo studies with Drosophila models confirmed that VCP selectively modulates aggregation and neurotoxicity induced by pathogenic Atx-3. Together, these results define the VCP-Atx-3 association as a potential target for therapeutic intervention and suggest that it might influence the progression of spinocerebellar ataxia type 3.